Tindak Tutur Ekspresif Guru dalam Pembelajaran Teks Prosedur Siswa Kelas VII SMP Negeri 1 Sungai Penuh - Fadila Amanda Meriska; Tressyalina; Syahrul R; Herlin Triana ((JPAP) Jurnal Praktisi Administrasi Pendidikan, 2026)
This study aims to analyze the expressive speech acts of teachers in the teaching of Procedural Texts of grade VII students of SMP Negeri 1 Sungai Penuh. Expressive speech acts are to analyze the use of expressive speech acts by teachers in the learning process, especially in teaching procedural texts. Expressive speech acts are one category of speech acts that function to convey the feelings or emotions of the speaker, such as thanking, apologizing, or congratulating. In the context of education, the use of expressive speech acts by teachers is expected to increase interaction and effective communication between teachers and students. This type of research is qualitative research with descriptive methods. The data in this study are the expressive speech acts of Indonesian language teachers of grade VII of SMP Negeri 1 Sungai Penuh. The research instrument is the researcher herself. Data collection techniques used in this study are sblc (free listening, engaging conversation), recording techniques and note-taking techniques. The results of the study indicate that teachers use various forms of expressive speech acts in learning, contributing to a positive learning atmosphere and supporting student engagement. This study also found that teachers' use of appropriate language and expressive speech acts can help students better understand the subject matter. Furthermore, this study emphasized the importance of language skills in establishing positive social relationships and interactions in the classroom. Thus, expressive speech acts play a crucial role in supporting the success of Indonesian language learning in the classroom.